Rancangan Produksi Kegiatan Pengupasan Lapisan Tanah Penutup Tambang Batubara PT Bumi Merapi Energi di Kecamatan Merapi Barat, Kabupaten Lahat, Provinsi Sumatera Selatan - Zulian Fariz; Iswandaru; Zaenal (Bandung Conference Series: Mining Engineering, 2022)
Abstract. PT Bumi Merapi Energi is one of the companies engaged in coal mining with an IUP area of 1,881 Ha located in West Merapi District, Lahat Regency, South Sumatra Province. PT Bumi Merapi Energi began land acquisition in 2015 and began its first mining activities in August 2015. PT Bumi Merapi Energi talah set a coal mining production target of 30,000 tons / month and a production target for overburden of 150,000 BCM / month at a Stripping Ratio of 5:1. Production planning is a production target plan for both overburden and coal on a monthly basis based on the total overburden volume and total coal volume per year and based on the efficiency of tool performance and the productivity of the loading and unloading equipment. This production planner is also used as a guide to determine the limits of mining progress on a monthly basis. Production planning and mining scheduling to be made must be in accordance with the production targets and stripping ratio values that have been set as well as the production value of each digging tool and transportation equipment so that data collection is needed in the form of direct observations in the field such as the productivity of the tools used, determination of work efficiency to plan the number of tools to be used, as well as determination of mining sequance and scheduling in accordance with production targets company. The production plan and mining scheduling are based on the calculation of the production of digging and transport equipment, the production plan obtained from January to December for overburden of 150,000 BCM / month and for coal of 30,000 tons / month. For the determination of sequences and disign pits carried out based on production targets so that coal was obtained in January amounting to 27,932 tons, February at 29,743 tons, March at 30,123 tons, April at 28,942 tons, in May at 29,742 tons, in June at 30,042 tons, in July at 30,238 tons, in August at 30,452 tons, in September at 28,042 tons, in October it was 30,642 tons, in November it was 28,042 tons, and in December it was 28,426 tons. Based on the results of research conducted to achieve the production target and the Stripping Ratio value that has been set by the company, it can be recommended the number of digging tools that can be used every month, namely as many as 4 units of Excavators and 32 units of Dumptruck. Abstrak. PT Bumi Merapi Energi merupakan salah satu perusahaan yang bergerak dalam bidang pertambangan batubara dengan luas wilayah IUP sebesar 1.881 Ha yang terletak di Kecamatan Merapi Barat, Kabupaten Lahat, Provinsi Sumatera Selatan. PT Bumi Merapi Energi mulai membebaskan lahan pada tahun 2015 dan mulai melakukan kegiatan penambangan pada bulan Agustus tahun 2015. PT Bumi Merapi Energi menentukan target produksi penambangan batubara sebesar 30.000 ton/bulan dan target produksi untuk overburden sebesar 150.000 BCM/bulan pada Stripping Ratio 5 : 1. Perencanaan produksi didasarkan pada target produksi, baik untuk overburden maupun batubara pada setiap bulan. Hal ini berdasarkan total volume overburden dan total volume batubara serta berdasarkan efisiensi kinerja alat dan produktivitas alat gali-muat dan angkut. Perencanaan produksi ini juga digunakan sebagai panduan untuk menentukan batas kemajuan penambangan pada setiap bulannya. Perencanaan produksi dan penjadwalan penambangan yang akan dibuat harus sesuai juga dengan nilai Stripping Ratio yang sudah ditetapkan serta nilai produksi dari setiap alat gali-muat dan alat angkut. Untuk itu dibutuhkan pengambilan data berupa pengamatan langsung di lapangan seperti produktivitas alat yang digunakan, penentuan effisiensi kerja untuk merencanakan jumlah alat yang akan digunakan, serta penentuan sequance dan penjadwalan penambangan yang sesuai dengan target produksi perusahaan. Target produksi dan penjadwalan penambangan dengan menggunakan alat gali-muat dan angkut pada bulan Januari sampai bulan Desember untuk overburden sebesar 150.000 BCM/bulan dan untuk batubara sebesar 30.000 ton/bulan. Penentuan sequence dan disign pit yang dilakukan berdasarkan target produksi dan didapatkan batubara pada bulan Januari sebesar 27.932 ton, Februari sebesar 29.743 ton, bulan Maret sebesar 30.123 ton, bulan April sebesar 28.942 ton, bulan mei sebesar 29.742 ton, bulan Juni sebesar 30.042 ton, bulan Juli sebesar 30.238 ton, bulan Agustus sebesar 30.452 ton, bulan September sebesar 28.042 ton, bulan Oktober sebesar 30.642 ton, bulan November sebesar 28.042 ton, dan bulan Desember sebesar 28.426 ton. Berdasarkan hasil penelitian yang dilakukan untuk mencapai target produksi dan nilai Stripping Ratio yang sudah ditetapkan oleh perusahaan, maka dapat direkomendasikan jumlah alat gali-muat yang digunakan pada setiap bulannya sebanyak 4 unit excavator dan 32 unit dumptruck.